Magies de la répétition - Prak-Derrington, Emmanuelle (Langages, 2021)
Heartbeats, alternation of night and day or seasons, Monday mornings... Our lives are made of repetitions. But what about repetition in language? Verbal repetition, long neglected as an area of study, is today being examined through numerous studies that tackle its specific aspects: approaches based on figures, authors, texts or type of speech. For the first time, a unitary definition of repetition is presented. What changes when sounds, words, phrases are said multiple times? How does speech serve anything other than the transmission of information? Why is repetition used in lyrical, political, religious and magical practices? These questions and many more are presented and examined by the author, who has been thinking and writing for years about verbal repetition. Written from a broadly interdisciplinary perspective, this book is aimed not only at linguists but at all those who are interested in the power of words.